2011
DOI: 10.21002/jaki.2011.05
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Kualitas Audit, Debt Default Dan Opinion Shopping Terhadap Penerimaan Opini Going Concern

Abstract: Responsibilities of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also assess the company's ability to maintain its survival. This is due to the demands of the shareholders to the auditor to provide early warning about the prospects of a company as consideration before deciding on an investment decision. The research's goals were to examine the effect of audit quality, debt default, and opinion shopping from going concern opinion. The samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
34

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 14 publications
2
22
0
34
Order By: Relevance
“…In other words Auditor only give opinions about going concern if the company had difficulty continuing its survival. This is confirmed by studies that have been done previously which found that the better financial condition of the company, the less the auditor gives going concern audit opinion [18,21,14,12,7,13,17,11,16].…”
Section: The Financial Condition Of the Company And Going-concern Audsupporting
confidence: 71%
See 2 more Smart Citations
“…In other words Auditor only give opinions about going concern if the company had difficulty continuing its survival. This is confirmed by studies that have been done previously which found that the better financial condition of the company, the less the auditor gives going concern audit opinion [18,21,14,12,7,13,17,11,16].…”
Section: The Financial Condition Of the Company And Going-concern Audsupporting
confidence: 71%
“…So that it is possible for the agency to act or behave deviate from fulfilling its interests Shareholders [6]. This is also corroborated by Praptitorini and Januarti [13] that however, managers do not always act according to the desire of shareholders, in part because of the presence of moral hazard.…”
Section: Agency Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Beberapa penelitian sebelumnya menunjukkan faktor-faktor yang memengaruhi opini audit going concern antara lain kualitas audit, audit lag, opini audit tahun sebelumnya, dan auditor client tenure (Januarti, 2009), current ratio (Bruynseels dan Willekens, 2006;Rahayu, 2007;Masyitoh dan Adhariani, 2010), leverage (Rudyawan dan Badera, 2008), profi tabilitas (Sartono, 2009;Behn et al, 2001;Hani dkk, 2003;Rahayu, 2007). Selain itu penelitian lainnya meneliti pengaruh rasio cash fl ow to total debt ratio (Mutchler, 1985;Mills dan Yamamura, 1998;Masyitoh dan Adhariani, 2010), ukuran perusahaan (Kevin et al, 2006;Ramadhany, 2005;Januarti dan Fitrianasari, 2008), pertumbuhan perusahaan (Altman, 1968;Fanny dan Saputra, 2005;Setyarno dkk., 2006), kualitas audit (DeAngelo, 1981;Setyarno dkk., 2006;Praptitorini dan Januarti, 2007). Audit lag juga diteliti oleh beberapa penelitian sebelumnya sebagai salah satu faktor yang memengaruhi opini audit going concern antara lain oleh Lennox( 2002), Putra (2010), Januarti (2009), Ramadhany (2004, Setyarno dkk.…”
Section: Latar Belakang Masalahunclassified
“…Fenomena ini disebut dengan opinion shopping. Lennox (2000) dalam Mirna Dyah Praptitorini (2007) dalam penelitiannya berpendapat bahwa perusahaan yang mengganti auditor (switching auditor) menurunkan kemungkinan mendapatkan opini audit yang tidak diinginkan, daripada perusahaan yang tidak melakukan pergantian auditor. Perusahaan yang berhasil dalam opinion shopping melakukan pergantian auditor dengan harapan mendapat opini wajar tanpa pengecualian dari auditor baru.Lennox (2002) dalam penelitiannya membuktikan bahwa opinion shopping berpengaruh signifikan terhadap opini audit going concern.…”
unclassified